Sanitation coverage and diarrhea outcomes among children aged under five years in Matabeleland, South Province of Zimbabwe - Sibanda, Brightwell; Susanna, Dewi (Journal of Health Education, 2024)
Background: Diarrhea remains a prominent factor contributing to the high rate of child mortality, particularly observed in children under the age of five. This study assessed the relationship between sanitation coverage and diarrhea outcomes among children under five in Matabeleland, South Province of Zimbabwe. Methods: The study utilized a quantitative cross-sectional study using a Demographic Health Survey and assesses from the 2019 Multiple Indicator Cluster Survey (MICS). This data is freely available at https://mics.unicef.org/surveys. A total of 518 mothers were analyzed in this research based on the secondary data from the 2019 MICS findings. The variables studied were the mother's education, wealth, handwashing, sanitation coverage, shared sanitation facilities, child age, residence, and religion. Results: The analysis revealed significant associations for both the age of the child and residence in Matabeleland, South Province; for age, the p-value was 0.039 with an OR of 0.594 and a 95% Confidence Interval (0.362-0.974), and residence with a p-value of 0.004 and OR of a 95% CI (1.329-4.484). Conclusion: sanitation coverage was not significant in this study. Therefore, health and hygiene education campaigns should be conducted to equip caregivers with adequate knowledge that is essential for the prevention of diarrhea.